An Analysis Illocutionary and Perlocutionary Found In “Mission: Impossible-Fallout - Andreawan, Ngakan Nyoman Bambang; Hilda Hastuti; Puspita Dewi (CV Insan Kreasi Media, 2022)
This study aims to describe the form of illocution speech acts and the effect of perlocution speech acts in the movie Mission: Impossible-Fallout. This study is a descriptive quantitative and qualitative. The instrument used in this study is the movie and transcript of Mission: Impossible-Fallout, which contains the understanding of speech acts in the study of pragmatic theory. The data collection method in this study is observation and note-taking technique. The results of this study indicate that there are 4 (representative 22.22%, directive 29.62%, expressive 25.92% and commissive 22.22%) of the 5 forms of illocution speech acts used in the transcript of the movie Mission: Impossible-Fallout with the effect of perlocution. Representative speech acts have state, speculate and report functions. Directive speech acts have order, urge and cue functions. Expressive speech acts have the functions of blame, praise and apologize. Commissive speech acts have the function of ability and promise. Then at the end of the speech act produces the effect of the speech act perlocution.